Cost-effectiveness analysis of the Grameen Bank of Bangladesh - Schreiner, Mark (2003)
Compares output with subsidy for the Grameen Bank in a present-value framework. Suggests that the Bank - if not necessarily other microlenders - was probably a worthwhile social investment.